From Global Financial Crisis to post-COVID: Mapping the transition in Sukuk research - Ali, Hassnian; Jafar, Ahmad (Journal of Islamic Economics Lariba, 2024)
IntroductionThe financial sector has experienced substantial changes throughout history, and sukuk has gained widespread recognition as a reliable funding option.ObjectivesThis study explores the evolution and impact of Sukuk financing from the Global Financial Crisis to the post-COVID era, emphasizing its importance within Islamic finance and its broader economic implications.MethodUsing a bibliometric analysis approach, data were extracted from the Scopus database, focusing on 287 English-language research articles containing "Sukuk" in their titles. Advanced bibliometric tools such as R’s Biblioshiny package and Microsoft Excel facilitated a quantitative assessment of publication trends, authorship, and thematic developments in Sukuk research.ResultsThe findings highlight a significant expansion in Sukuk-related research, with diversification in themes such as sustainability, governance, and innovation in Islamic finance. Key contributors and influential works were identified, showing a shift towards addressing contemporary financial challenges through Islamic principles. While the study acknowledges limitations in scope due to its bibliometric approach, it suggests that future research could incorporate more qualitative analyses to deepen the understanding of emerging trends.ImplicationsThe insights from this study provide valuable guidance for practitioners, policymakers, and investors in Islamic finance, underlining the role of Sukuk in promoting sustainable economic growth and financial stability. Additionally, the findings demonstrate the potential of Sukuk to contribute to ethical and socially responsible investment, aligning financial practices with broader societal values.Originality/NoveltyThis study adds to academic discourse by offering a comprehensive overview of Sukuk literature’s evolution and serves as a foundational resource for further investigation and practical application in the field of Islamic finance.